Pride in foreign language learning: a conceptual framework and empirical evidence - Khajavy, Gholam Hassan; Lüftenegger, Marko (Innovation in language learning and teaching, 2025)
Previous studies have found that pride is a frequent and important emotion in achievement contexts although it is under-researched in the second/foreign language (FL) context. Therefore, the aim of this research was to explore pride in the context of FL learning. For this purpose, we proposed a conceptual model of FL pride, drawing on previous theoretical frameworks, which distinguishes four types of pride: self-based, social comparison-based, praise-based, and help-based. Then, to test this model, we conducted two studies. In Study 1, we asked participants to recall events that they felt pride during the FL process. In Study 2, we developed and validated foreign language pride scale (FLPS). Results of confirmatory factor analysis indicated that FL pride is best represented by a higher-order model. We further investigated its criterion-related validity by examining the relations between FL pride and theoretically relevant constructs and found that it is related to several motivational, emotional, and outcome measures.